Answer:
D. 32.
Step-by-step explanation:
![3x^2 - 4\\= 3^2 * 2\\= 6^2 - 4\\= 36 - 4\\= 32.](https://tex.z-dn.net/?f=3x%5E2%20-%204%5C%5C%3D%203%5E2%20%2A%202%5C%5C%3D%206%5E2%20-%204%5C%5C%3D%2036%20-%204%5C%5C%3D%2032.)
hope this helps.
Answer:
y = -7/6x
Step-by-step explanation:
y - y1 = m*(x-x1)
m=y/x
y - (-7) = -7/6*(x-6)
y + 7 = -7/6x + 7
y = -7/6x + 7 - 7
y = -7/6
Answer:
Step-by-step explanation:
Answer:
30
Step-by-step explanation:
f(-5) = -7(-5) - 5
= 35 - 5 = 30
Answer:
1.7
Step-by-step explanation: